Health problems of a patient affected by Buerger’s disease - Malinowska-Lipień, Iwona; Gabryś, Teresa; Kruczek, Katarzyna; Brzostek, Tomasz; Kawalec, Ewa; Reczek, Agata (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. The thromboangiitis obliterans (TAO) is a disease usually occurring among young men. It ordinarily arises at the age between thirty and forty years, especially among cigarette smokers. A significant role in the therapeutical and nursing-care process is played by the planning of care based on the observation of the patient’s health needs and problems. The work presents a patient’s health problems on the basis of their case study. Purpose of work. analysis of the biopsychosocial situation of the patient affected by Buerger’s disease; specification of the patient’s health problems. Material and methods. A medical history was described with regard to a patient suffering from Buerger’s disease, that accomplished by employing the method of their individual case. The research techniques included interviews with the patient and the medical staff, analysis of medical records, and day-to-day observation of the patient during their stay at the angiology ward. The study was conducted for the duration of the patient’s 18-day hospital-stay period, following the patient’s prior consent obtained for the conduct of the study. Results. Ten nursing-care problems were diagnosed in the patient, out of which the most prominent was the deficit of self-care caused by chronic pain, right-foot ulceration, and depression. In the course of the patient’s stay at the angiology ward, the effects achieved included an alleviation of their pain complaints, a reduction of ulceration areas, an increase of psychophysical activity, mood enhancement. Conclusions. As a result of the therapeutical and nursing-care procedures that had been adopted, the patient was able, when leaving the hospital, to exercise self-care with respect to safe movement, selfobservation focussing on the course of the disease, the rules of feet care, physical activity, application of a diet, taking prescribed medication, regular follow-up evaluations at an angiology outpatient clinic. The patient requires emotional, information-related, and social support and encouragement provided on a regular basis.